Design and implementation of a lightweight security model to prevent IEEE 802.11 wireless DoS attacks. - Malekzadeh, Mina; Abdul Ghani, Abdul Azim; Subramaniam, Shamala (Hindawi Publishing Corporation, 2011)
The protection offered by IEEE 802.11 security protocols such as WEP, WPA, and WPA2 does not govern wireless control frames. The control frames are transmitted in clear-text form, and there is no way to verify their validity by the recipients. The flaw of control frames can be exploited by attackers to carry out DoS attacks and directly disrupt the availability of the wireless networks. In this work, focusing on resource limitation in the wireless networks, a new lightweight noncryptographic security solution is proposed to prevent wireless DoS attacks. In order to prove the ability of the proposed model and quantify its performance and capabilities, a simulation topology is developed, and extensive experiments are carried out. Based on the acquired results, it is concluded that the model successfully prevents wireless DoS attacks, while the security cost is not remarkable compared to the model achievements.